Did high sugar-sweetened beverage purchasers respond differently to the excise tax on sugar-sweetened beverages in Mexico? - Ng, Shu Wen (Public Health Nutr, 2018)
OBJECTIVE: To estimate changes in taxed and untaxed beverages by volume of beverage purchased after a sugar-sweetened beverage (SSB) tax was introduced in 2014 in Mexico. DESIGN: We used household purchase data from January 2012 to December 2015. We first classified the sample into four groups based on pre-tax purchases of beverages: (i) higher purchases of taxed beverages and lower purchases of untaxed beverages (HTLU-unhealthier); (ii) higher purchases of both types of beverages (HTHU); (iii) lower purchases of taxed and untaxed beverages (LTLU); and (iv) lower purchases of taxed beverages and higher purchases of untaxed beverages (LTHU-healthier). Next, we estimated differences in purchases after the tax was implemented for each group compared with a counterfactual based on pre-tax trends using a fixed-effects model. SETTING: Areas with more than 50 000 residents in Mexico. PARTICIPANTS: Households (n 6089). RESULTS: The HTLU-unhealthier and HTHU groups had the largest absolute and relative reductions in taxed beverages and increased their purchases of untaxed beverages. Households with lower purchases of untaxed beverages (HTLU-unhealthier and LTLU) had the largest absolute and relative increases in untaxed beverages. We also found that among households with higher purchases of taxed beverages, the group with lowest socio-economic status had the greatest reduction in purchases of taxed beverages. CONCLUSIONS: Evidence associating the SSB tax with larger reductions among high purchasers of taxed beverages prior to the tax is relevant, as higher SSB purchasers have a greater risk of obesity, diabetes and other cardiometabolic outcomes.